2008
DOI: 10.1289/ehp.11272
|View full text |Cite
|
Sign up to set email alerts
|

Recent Mortality from Pleural Mesothelioma, Historical Patterns of Asbestos Use, and Adoption of Bans: A Global Assessment

Abstract: BackgroundIn response to the health risks posed by asbestos exposure, some countries have imposed strict regulations and adopted bans, whereas other countries have intervened less and continue to use varying quantities of asbestos.ObjectivesThis study was designed to assess, on a global scale, national experiences of recent mortality from pleural mesothelioma, historical trends in asbestos use, adoption of bans, and their possible interrelationships.MethodsFor 31 countries with available data, we analyzed rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
107
0
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(122 citation statements)
references
References 22 publications
7
107
0
8
Order By: Relevance
“…These trends are consistent with previous reports 9, [21][22][23] and may reflect the wax and wane of disease with historical asbestos use. 24 Accordingly, the burden of disease may be shifting towards countries that used asbestos more recently, such as those in Asia and, to a lesser extent, middleand low-income countries.…”
Section: Discussionmentioning
confidence: 99%
“…These trends are consistent with previous reports 9, [21][22][23] and may reflect the wax and wane of disease with historical asbestos use. 24 Accordingly, the burden of disease may be shifting towards countries that used asbestos more recently, such as those in Asia and, to a lesser extent, middleand low-income countries.…”
Section: Discussionmentioning
confidence: 99%
“…Asbestos exposure was first identified as a cause of MPM in the 1960's, and it is estimated that up to 80% of cases of MPM are related to asbestos exposure with the onset of disease generally occurring 20-70 years after exposure through mechanisms of chronic inflammation (3)(4)(5). The incidence of MPM in the United States has stabilized over the past few years likely due to decreased asbestos use since the 1970's (1); however, the incidence of MPM in developing countries is expected to increase and represents a substantial health and economic burden (6,7). Risk factors for mesothelioma also include environmental, occupational, and para-occupational exposure to asbestos and other mineral fibers such as erionite (8).…”
Section: Introductionmentioning
confidence: 99%
“…The geographic distribution of the tumor is relevant with reference to its etiology. Various studies have revealed a relationship between mesothelioma incidence at a country level and consumption of asbestos in the previous decades (Tossavainen, 2003;Tossavainen, 2004;Lin et al, 2007;Nishikawa et al, 2008). Moreover, in a given country the areas with high mesothelioma incidence exactly correspond to the location of the industries and activities, in which asbestos use has been heavy .…”
Section: Introductionmentioning
confidence: 98%